2007
DOI: 10.1007/s00192-007-0399-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual function in women after surgery for pelvic organ prolapse

Abstract: Our objective was to evaluate the effect of surgical repair of pelvic organ prolapse on female sexual function. Sixty seven women with pelvic organ prolapse were recruited in the study. Degree of pelvic organ prolapse was assessed using pelvic organ prolapse quantitation (POPQ) staging system. Female sexual function index (FSFI) questionnaire was used to assess sexual function of the cases preoperatively and 12-16 weeks after the operation. Mean age of the cases was 36.03 +/- 5.38 years. The total mean FSFI sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 28 publications
2
32
0
3
Order By: Relevance
“…Azar et al [41] noted similar results in a cohort of 60 patients following repair of a variety of pelvic organ prolapses without mesh or grafts. The authors reported a significant postoperative decrease in dyspareunia per the FSFI scale at 15 weeks.…”
Section: Pelvic Organ Prolapse Surgerysupporting
confidence: 59%
“…Azar et al [41] noted similar results in a cohort of 60 patients following repair of a variety of pelvic organ prolapses without mesh or grafts. The authors reported a significant postoperative decrease in dyspareunia per the FSFI scale at 15 weeks.…”
Section: Pelvic Organ Prolapse Surgerysupporting
confidence: 59%
“…Currently, the evidence regarding sexual function and rates of dyspareunia following surgical repair of POP varies widely. Some studies have shown a decline in sexual function [10,11], whereas others have shown no change [12,13] or improvement [14][15][16]. In a study by Altman et al [10 they noted an approximately 15 % rate of dyspareunia before surgery, which decreased to 12 % in those with anterior vaginal mesh repairs.…”
Section: Introductionmentioning
confidence: 99%
“…Parmi les é tudes prospectives sur la ré paration chirurgicale vaginale, six [14][15][16][17][18][19] dé crivent une amé lioration significative aprè s chirurgie mais seulement trois utilisent des questionnaires validé s. Cinq auteurs ne trouvent pas de modification de la sexualité aprè s chirurgie vaginale [20][21][22][23][24] dont trois avec des questionnaires validé s. Trois é tudes [25,7,26] retrouvent une possible aggravation. Cette aggravation ne semble pas corré lé e à la diminution des dimensions vaginales même s'il existe une ré duction significative de la taille du vagin en postopé ratoire [26].…”
Section: Sexualiteńunclassified